Experimental planning to feasibilize the use of scheelita waste as a small aggregate in interlocked floors (Research, Society and Development, 2022)
The mining sector in Brazil is one of the sectors that generate the most waste, polluting surface and underground water resources and also the soil. The proper management of this waste through its use in civil construction, more specifically in alternative materials, is one way to minimize these impacts to the environment. In this sense, this paper aims to propose an appropriate destination for the scheelite mining waste, reusing it in concrete as a partial replacement of the fine aggregate used in interlocking sidewalks, from the study of experimental planning of mixtures. The physical, chemical and mineralogical characterization of the waste and conventional materials, coarse aggregate and binder were performed according to ABNT standards. Next, a study of the conventional mixtures was performed, by the experimental dosage method, which served as a comparative basis when the waste was partially substituted, based on the results of the RCS and absorption tests. The experimental planning of mixtures and the analysis of response surfaces reveal the ideal proportions for incorporating the waste in the concrete. It is verified that the experimental planning of mixtures of the simple network proves to be efficient for the verification of ideal parameters of composition, presenting a good standard of data quality, facilitating the study in the analysis of homogeneous materials such as concrete. It can be concluded that the concrete for interlocked paving purposes containing only the scheelite waste as fine aggregate is satisfactory according to current Brazilian standards, making it a viable alternative for the insertion of waste.